2020
DOI: 10.3961/jpmph.20.094
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rumors and Misinformation on COVID-19 in Social Media

Abstract: PerspectiveThe coronavirus disease 2019 (COVID-19) pandemic has not only caused significant challenges for health systems all over the globe but also fueled the surge of numerous rumors, hoaxes, and misinformation, regarding the etiology, outcomes, prevention, and cure of the disease. Such spread of misinformation is masking healthy behaviors and promoting erroneous practices that increase the spread of the virus and ultimately result in poor physical and mental health outcomes among individuals. Myriad incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
459
2
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 614 publications
(481 citation statements)
references
References 3 publications
2
459
2
18
Order By: Relevance
“…Mass media and social media are easily accessible to the public. However, the information is sometimes inaccurate and incomplete (Shu, Sliva, Wang, Tang, & Liu;Tasnim, Hossain, & Mazumder, 2020). The study found that the public has made efforts to avoid fake news about COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Mass media and social media are easily accessible to the public. However, the information is sometimes inaccurate and incomplete (Shu, Sliva, Wang, Tang, & Liu;Tasnim, Hossain, & Mazumder, 2020). The study found that the public has made efforts to avoid fake news about COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings on the harms of social media rumors and misinformation surrounding COVID-19 also demonstrate the detrimental effects of online myth propagation. Improper use of pharmacological drugs and panic buying have resulted from online COVID-19 myths [ 57 ], as well as concern over the disease being spread through meat consumption and Chinese biological military laboratories [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the article titled "Impact of rumors and misinformation on COVID-19 in social media" published in your esteemed journal [1]. As a continuation of the points made in that article, in this letter, we would like to discuss how technology and social media are being or should be leveraged to fight the coronavirus disease 2019 (COVID-19) "infodemic" and COVID-19-related misinformation in India.…”
Section: Dear Editormentioning
confidence: 98%